Is There a Possible Neuropathic Pain Component in Knee Osteoarthritis? - Cemile Sevgi POLAT; Asuman DOĞAN; Didem SEZGİN ÖZCAN and Belma Füsun KÖSEOĞLU and Sinem KOÇER AKSELİM (Archives of Rheumatology, 2017)
Objectives: This study aims to investigate the neuropathic pain (NP) component in patients with osteoarthritis (OA) of the knee and its association with physical function, risk factors, and stages of OA. Patients and methods: One hundred and nine patients (16 males, 93 females; mean age 62.5±8.5 years; range 44 to 81 years) diagnosed with knee OA according to the American College of Rheumatology criteria were enrolled in this study between July 2014 and June 2015. Patients were evaluated with visual analog scale for pain severity, PainDETECT questionnaire for presence and severity of neuropathic pain, Western Ontario and McMaster Universities osteoarthritis index for physical function, and the Kellgren-Lawrence system for severity of OA. Presence of the associated risk factors were also questioned. Results: A total of 12 patients (11%) were classified as having likely NP and 23 patients (21.1%) were classified as having possible NP. PainDETECT scores were significantly correlated with the visual analog scale scores and Western Ontario and McMaster Universities osteoarthritis index pain, physical function and total scores. Patients with neuropathic pain had significantly longer symptom duration than the patients without NP. However, we found no relationship between the other risk factors and NP. Conclusion: This study demonstrated that some of the knee OA patients had a NP component as the underlying cause of knee pain. Patients with NP had longer symptom duration, increased severity of pain, and disability. Therefore, the presence of NP component in these patients should be considered. Once it is determined, appropriate intervention strategies for NP should be incorporated in the routine treatment modalities of knee OA.